Enzyme Selectivity Fine‐Tuned through Dynamic Control of a Loop. (28th January 2016) - Vögeli, Beat; Bibow, Stefan; Chi, Celestine N.
Abstract: Allostery has been revealed as an essential property of all proteins. For enzymes, shifting of the structural equilibrium distribution at one site can have substantial impacts on protein dynamics and selectivity. Promising sites of remotely shifting such a distribution by changing the dynamics would be at flexible loops because relatively large changes may be achieved with minimal modification of the protein. A ligand‐selective change of binding affinity to the active site of cyclophilin is presented involving tuning of the dynamics of a highly flexible loop. Binding affinity is increased upon substitution of double Gly to Ala at the hinge regions of the loop. Quenching of the motional amplitudes of the loop slightly rearranges the active site. In particular, key residues for binding Phe60 and His126 adopt a more fixed orientation in the bound protein. Our system may serve as a model system for studying the effects of various time scales of loop motion on protein function tuned by mutations.